Strengthening Regulations towards Implementation of Intellectual Property-Based Financing Scheme with YouTube Content as Collateral - Pasha, Ishtar Amarindra; Abubakar, Lastuti; Muchtar, Helitha Novianty (Jurnal Ius Constituendum, 2024)
This research aims at examining how the regulator can make regulation to optimize financing implementation with YouTube content as a collateral. This research is considered necessary, because besides Government Regulation Number 24 Year 2022 which becomes the basis to give financing under an intellectual property as a collateral, banking institutions might still be in doubt to implement such a financing scheme due to many weak supporting regulations. This research is conducted with a normative-juridical approach method. The research shows that there are still many regulations which have not accommodated the financing implementation of intellectual property-based financing scheme basis, especially those regulations related to valuation, recognition of intellectual property as a banking asset and execution of intellectual property when a debtor default. The weak regulation of these three aspects makes financial institutions doubtful to implement the intellectual property-based financing especially because bank activities are to collect and distribute funds to the society. The conclusions of this research show that basically there has been a method or way to anticipate the three problems, but it needs to be legalized in a form of regulation so that the bank has legal certainty and protection in its financing with intellectual property as the collateral. The regulators are supposed to be able to create regulation to optimize financing implementation with intellectual property as the collateral.